5n + 7 = 7(n+1) - 2n
First distribute 7 to all terms inside the parenthesis
7(n) = 7n
7(1) = 7
5n + 7 = 7n - 2n + 7
Simplify. Combine like terms
5n + 7 = 5n + 7
True.
If you want to continue:
Isolate the n, move all variables to one side, and constants to the other
5n (-5n) + 7 (-7) = 5n (-5n) + 7 (-7)
0 = 0
True
hope this helps
0.10d + 0.25q = 3.55
q = d + 3
0.10d + 0.25(d + 3) = 3.55
0.10d + 0.25d + 0.75 = 3.55
0.10d + 0.25d = 3.55 - 0.75
0.35d = 2.80
d = 2.80/0.35
d = 8.....8 dimes
q = d + 3
q = 8 + 3
q = 11 <=== 11 quarters
30 I believe, sorry if I am wrong, I am bad at math and history.
Answer:
answer...
Step-by-step explanation:
This is the answer.